The resort areas of the Adriatic Coast of Croatia: the peculiarities of the development of tourism in the region - Onatskiy, Maksim (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism, 2019)
The article is devoted to the investigation of the resort potential of the Adriatic coast of Croatia. Tourism is one of the main branches of Croatia’s economy which contributes the most part of the profits to this country’s budget. Among the most popular types of tourism is tourism in order to relax and get new impressions. And the government of Croatia, and business-structures as well, demonstrated the ability of using the tourist potential of the country very effectively. This experience can become very useful for many states of the world. The subject of the investigation is the resort areas of the Adriatic coast of Croatia. The goal of the article is to analyze the peculiarities of the development of tourism of the Adriatic coast. To achieve this goal the author raises the following tasks: to reveal the reasons of the transformation of the Adriatic coast into the main resort region of Croatia; to determine the specificity of the tourism development in this region; to point out the role and place of tourism branch in the country’s economy. In this investigation the following scientific methods are used: the analysis, the synthesis, the induction, the deduction. The results of the investigation enable the author to arrive at the following conclusions. The key role in the transformation of the Adriatic coast into the main resort area of Croatia was played by its high tourism and recreational potential. In the course of tourism development the rich historical and cultural heritage is effectively used, as well as natural virgin land fund of this region. The features of the development of tourism in the region are revealed. Identified trends in the development of tourist business in Croatia. The peculiarity of the tourism development of the Adriatic coast is the opportunity of uniting several kinds of tourism. The main stream of tourists to Croatia consist, first of all, of tourists from the EU countries and from the North America states. The profits from tourism amount about 25 per cent of the GDP of the country.